2014
DOI: 10.1111/jphp.12209
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between valproic acid and quetiapine/olanzapine in the treatment of bipolar disorder and the role of therapeutic drug monitoring

Abstract: Objectives The anticonvulsant valproic acid and the atypical antipsychotics olanzapine and quetiapine provide synergistic mood-stabilising, antidepressant and antipsychotic activities in the treatment of bipolar and schizoaffective disorders. Existing literature shows that pharmacokinetic and pharmacodynamics drug-drug interactions (DDIs) possibly occur with the use of such a combination. Clinical reports of a possible interaction between the drugs leading to an increased risk of adverse drug reactions have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
(78 reference statements)
0
7
1
Order By: Relevance
“…Although valproic acid is not metabolized via CYP3A4 and CYP2D6 but via glucuronosyltransferase [9], it has been shown that co-medication with valproic acid was associated with a 77 % increase in quetiapine plasma concentration [19]. This interaction has been shown to be clinically relevant [20]. Because in our study only 6 of 180 patients were co-prescribed valproic acid, we were not able to demonstrate this pharmacokinetic drug interaction.…”
Section: Patientscontrasting
confidence: 55%
“…Although valproic acid is not metabolized via CYP3A4 and CYP2D6 but via glucuronosyltransferase [9], it has been shown that co-medication with valproic acid was associated with a 77 % increase in quetiapine plasma concentration [19]. This interaction has been shown to be clinically relevant [20]. Because in our study only 6 of 180 patients were co-prescribed valproic acid, we were not able to demonstrate this pharmacokinetic drug interaction.…”
Section: Patientscontrasting
confidence: 55%
“…There are reports in the literature noting increase in rare side effects following VPA coadministration with olanzapine and quetiapine, respectively. 20 VPA was noted to increase plasma concentration of quetiapine by 77% when coadministered. 21 An analysis on the interaction between VPA and olanzapine/quetiapine noted that VPA decreases plasma concentration of olanzapine and increases plasma concentration of quetiapine.…”
Section: Discussionmentioning
confidence: 94%
“…An early review on hematological side effects of psychotropic drugs mentions valproic acid as causing anemia, neutropenia, pure red cell aplasia and thrombocytopenia, and olanzapine as inducing leukocytosis and thrombocytopenia (19). Furthermore, recent evidence associates olanzapine with leukopenia, even recommending that the guidelines for using and monitoring olanzapine be reconsidered (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Use of psychotropic drugs with minimal liver metabolism and monitoring the levels of aminotransferases is considered appropriate in such occasions (28,29). Other ADRs that olanzapine and valproate share are weight gain, somnolence, tremor, dry mouth, and speech disorders (20).…”
Section: Discussionmentioning
confidence: 99%